2015
DOI: 10.9758/cpn.2015.13.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjunctive High Frequency Repetitive Transcranial Magnetic Stimulation of Right Prefrontal Cortex in Adolescent Mania: A Randomized Sham-Controlled Study

Abstract: ObjectiveTo examine the efficacy of adjunctive right prefrontal high-frequency repetitive transcranial magnetic stimulation (rTMS) treatment in adolescent mania patients as compared to sham stimulation.MethodsTwenty six right handed patients aged 12–17 years diagnosed with bipolar mania were randomized to receive daily sessions of active or sham rTMS (20 Hz, 110% of motor threshold, 20 trains, 10 s intertrain interval) over the right dorsolateral prefrontal cortex for 10 days. Mania was rated using Young Mania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…There were 81 adverse events that were attributed to rTMS protocols in the CNS disorder population (Table 2). The mild adverse events were as follows: headache (n=45) 15, 21, 64, 69-71, 75, 78 , dizziness (n=8) 66, 69, 70 , jaw twitching (n=4) 66 , nausea/vomiting (n=4) 21, 75 , anxiety (n=3) 69 , neck stiffness (n=3) 21 , tingling/dullness (n=3) 69, 75 , scalp pain (n=2) 13, 67 , neck pain (n=2) 70 , restlessness (n=1) 77 , and sleepiness (n=1) 14 . Moderate adverse events include generalized tonic-clonic seizure (n=3) 65, 68, 72 and rapid moodswings (n=1) 77 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 81 adverse events that were attributed to rTMS protocols in the CNS disorder population (Table 2). The mild adverse events were as follows: headache (n=45) 15, 21, 64, 69-71, 75, 78 , dizziness (n=8) 66, 69, 70 , jaw twitching (n=4) 66 , nausea/vomiting (n=4) 21, 75 , anxiety (n=3) 69 , neck stiffness (n=3) 21 , tingling/dullness (n=3) 69, 75 , scalp pain (n=2) 13, 67 , neck pain (n=2) 70 , restlessness (n=1) 77 , and sleepiness (n=1) 14 . Moderate adverse events include generalized tonic-clonic seizure (n=3) 65, 68, 72 and rapid moodswings (n=1) 77 .…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies of TMS for mania noted that patients reported side effects; across these studies, patients experienced pain during their procedure (which went away after session completion), dizziness, anxiety, and a brief headache following treatment (Pathak et al, 2015;Praharaj et al, 2009). Only two studies of TMS for mania noted that patients reported side effects; across these studies, patients experienced pain during their procedure (which went away after session completion), dizziness, anxiety, and a brief headache following treatment (Pathak et al, 2015;Praharaj et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received the active treatment demonstrated significant improvements in mania (as evaluated via the YMRS (Young et al, 1978)) relative to the sham group (Praharaj, Ram, & Arora, 2009). However, a follow-up study employing an identical protocol in an adolescent sample found no significant differences in mania outcomes between the active and sham groups (Pathak, Sinha, & Praharaj, 2015). The authors suggest that the discrepant findings between the two studies may be accounted for by metabolic differences between adults and chil- Abbreviations: CGI, Clinical Global Impressions Scale (Spearing et al, 1997); HAM-D, Hamilton Rating Scale for Depression (Hamilton, 1960); MADRS, Montgomery-Asberg Depression Rating Scale (Montgomery & Asberg, 1979); TMS, transcranial magnetic stimulation.…”
Section: Tms In Maniamentioning
confidence: 93%
See 2 more Smart Citations